Association between peripheral blood mononuclear cell ORMDL3 expression and the asthma predictive index in preschool children. Issue 8 (August 2019) - Li, Yaqin; Cao, Lanfang; Yu, Qing; Xue, Haiyan; Lu, Yanming
Objective: This study aimed to assess whether orosomucoid 1-like 3 (ORMDL3) expression and environmental and clinical factors are associated with wheezing episodes in preschool children. Methods: Children diagnosed with wheezing episodes were classified according to their asthma predictive index (API) in the past year as follows: API+ (≥4 wheezing episodes), API− (1–3 wheezing episodes), and API0 (without wheezing). ORMDL3 expression was assessed by real-time polymerase chain reaction in peripheral blood mononuclear cells (PBMCs). Receiver operating characteristic curve analysis of ORMDL3 expression and the API was performed for diagnosing wheezing episodes. Correlations between ORMDL3 expression and asthma risk factors were examined using Spearman's correlation. Results: PBMC ORMDL3 expression was higher in the API+ group compared with the API− and API0 groups. The area under the curve for ORMDL3 expression was 0.820 (95% confidence interval, 0.771–0.869). ORMDL3 expression was positively correlated with the API ( r  = 0.447), infantile eczema ( r  = 0.499), wheezing ( r  = 0.516), total immunoglobulin E ( r  = 0.208), and environmental factors, including Dermatophagoides pteronyssinus ( r  = 0.357), house dust mites ( r  = 0.112), dog fur ( r  = 0.226), and Aspergillus ( r  = 0.257). ORMDL3 expression was negatively correlated with amaranth ( r  = −0.122). Conclusions: ORMDL3 expression in PBMCs is positively associated with the API and some asthma-related clinical and environmental risk factors in preschoolers.